Cultural Value of Local Wisdom: Ritual Speech of the Marriage Process: Eastern Indonesia - ., Kasmawati; Maknun, Tajuddin; Bandung, A.B Takko; Hasjim, Munira (Journal of Ecohumanism, 2025)
The purpose of this study is to export cultural values in ritual speech in wedding processions. The theory used on this topic, namely: (Sibarani, 2015) regarding the value of welfare and kindness. The value was developed based on its description consisting of five values of local wisdom, namely beauty, cleanliness, purity, protection, and unifying, here are the findings: 1) Beauty values from traditional, physical, and natural local wisdom: (a) Traditional, powder from the month of birth from the sun. (b) physical, looking at many times and looking at them frequently. (c) Natural, as is the case with the fourteenth month. 2) Cleanliness of local wisdom spiritual, emotional, physical. (a) Spiritually, water will easily be seen in your life. (b) Emotional, his face radiates down from Muhammad (saw). (c) Physical, as is the fourteenth moon. 3) purity of local wisdom spiritual, emotional, and moral. (a) Spiritual, you are the sparkle in the sky. (b) Emotional, meet halal sustenance for people who are going to get married. (c) Moral, take the cleaner from him. 4) The value of protection from local social, cultural, and self-wisdom. (a) Social, I wear Karaeng Ciknong clothes. (b) I am covered in beautiful Daeng Bajik (culture). (c) Self: living in my life. 5) The unifying value of local social, spiritual, and humanitarian wisdom. (a) Social, I open the door smiling, I tap the wall laughing. (b) Spiritual, sitting in His heaven. (b) All beings see and praise you. (c) Humanity, give kindness to this woman, with what is in her. The value of local wisdom obtained in ritual speech is found in the form of the values of beauty, cleanliness, purity, protection, and the value of unifying. Suggestions for future research, the cultural values found can be relevant to oral traditions and modern life today.